2020
DOI: 10.3906/kim-2001-51
|View full text |Cite
|
Sign up to set email alerts
|

Application of synthesized copper nanoparticles using aqueous extract of Ziziphus mauritiana L. leaves as a colorimetric sensor for the detection of Ag+

Abstract: The presented work demonstrates the preparation of copper nanoparticles (CuNPs) via aqueous leaves extract of Ziziphus mauritiana L. (Zm) using hydrazine as a reducing agent. Various parameters such as volume of extract, concentration of hydrazine hydrate, concentration of copper chloride, and pH of the solution were optimized to obtain Ziziphus mauritiana L. leaves extract derived copper nanoparticles (Zm-CuNPs). Brownish red color was initial indication of the formation of Zm-CuNPs while it was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
2
2
1
Order By: Relevance
“…Much similar to our present results, Mali et al [26] . and Memon et al [38] . reported neutral pH (pH 7) as the optimum for the biosynthesis of CuNPs from the leaves extract.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Much similar to our present results, Mali et al [26] . and Memon et al [38] . reported neutral pH (pH 7) as the optimum for the biosynthesis of CuNPs from the leaves extract.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, stable formation of CuNPs was observed at pH 8 (Figure 1d) whereas aggregation was noticed at pH 9 and 10. Much similar to our present results, Mali et al [26] and Memon et al [38] reported neutral pH (pH 7) as the optimum for the biosynthesis of CuNPs from the leaves extract. Thus, the optimum medium (50 ml) containing 12 ml of leaves extract and 10 mM CuSO 4 ⋅ 5H 2 O turned into green color within 24 h at pH 8, indicating the formation of CuNPs.…”
Section: Biogenic Synthesis and Factors Influencing The Synthesis Of ...supporting
confidence: 93%
See 2 more Smart Citations
“…[ 25 ] Z. mauritiana is a potential plant both for food and phytomedicine applications The phytochemical analyses of Zizyphus mauritiana L leaves extract has already been investigated by many groups revealing that it contains a substantial amount of phenols, flavonoids, carbohydrates, alkaloids, proteins, and amino acids. [ 26 ] Plenty of studies have been conducted for the synthesis of silver [ 27 ],[ 28 ] gold, [ 29 ] copper, [ 30 ] and zinc [ 31 ] NPs using Z. mauritiana L. leaves extract.…”
Section: Introductionmentioning
confidence: 99%